2015–16 ENSO contributed reduction in oil sardines along the Kerala coast, south‐west India. (24th November 2019) - Shetye, Suhas S.; Kurian, Siby; Gauns, Mangesh; Vidya, Pottekkatt Jayapalan
Abstract: Fishery along the west coast of India largely depends on pelagic fish such as oil sardines, which are dominant during the south‐west monsoon. However, the response of sardine population to the warming caused by the climatic events such as El Niño/Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) is poorly studied. Here, we hypothesize that the ENSO‐related changes in biogeochemistry can adversely affect the oil sardines. We have used biogeochemical data collected along the Kerala coast during September 2015 (ENSO year) and September 2017 (a normal year) supported by catch per unit effort (CPUE) and fishery landing data to show the ENSO‐related bio‐physical dynamics and its impact on the oil sardine population along the south‐west coast of India. During the 2015 ENSO year, upwelling velocity decreased minimizing cooling of surface waters and resulted with an increase in sea surface temperature (SST) ( 1.8°C). Consequent decrease in nutrient levels favoured nano‐phytoplankton and pico‐phytoplankton. On the other hand, during September 2017 when the ENSO effect was nullified, the decreased SST and availability of nutrients in the euphotic zone resulted in the dominance of micro‐phytoplankton. The hydrographic conditions (reduction in upwelling intensity), and reduction in micro‐phytoplankton abundance and zooplankton density in turn perhaps affected the fishery potential of the region. Oil sardines population (along the west coast) collapsed from 1.55 lakh tones (2014) to 0.46 lakh tones during 2015–2016 ENSO event, while in 2017 the conditions become favorable and their population was back to normal (1.27 lakh tones). Our results are in close agreement with our hypothesis and suggest that ENSO events could reduce phytoplankton productivity and disrupt the food chain, which in turn can affect the oil sardine population along the west coast of India.